Avaliação dos sinais de EEG e dos potenciais evocados visuais durante estimulação visual dinâmica giratória - Mesquita, Michelle Araujo (2019)
This study aimed at developing a three-dimensional rotatory model of a carousel via Stereoscopic Virtual Reality to investigate the effects on cortical activation, causing Motion Visual Evoked Potential (M-VEP) and to induce orthostatic postural instability (OP). Twenty two healthy volunteers, between 18 and 40 years old, of both genders, were submitted, in OP, to multichannel EEG and stabilometry recording during dynamic visual stimulation (SD), using two rotational speeds (5 °/s and 25 °/s) clockwise. The Grand-Averaged M-VEP evidenced the P3 component, with larger amplitudes in the occipito-central-pariental region. The running t-test indicated that, within the range from 656 to 943 ms after SD, GrandAverage differed between high and low speeds. Increased entropy suggests parallel processing of the information of the scenarios objects. The synchronization/desynchronization index (ERD/ERDS) showed the highest occurrence of synchronism, for the high speed, in the frequency of Theta band in the occipital derivation and, for the low speed, in the occipital derivation of the Alpha and Beta bands. The results of the stabilometry indicated that using rotatory cylinder during dynamic visual stimulation, it’s possible to detect the variation of the individual’s center of pressure in low speed